Larvicidal Effects of Citrus Peels Extracts against Culex Pipiens Mosquitoes - Abiodun Obembe; Opeyemi Gbenga Oso (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Mosquitoes transmit severe diseases such as malaria, lymphatic filariasis, dengue fever, and yellow fever. These diseases result in significant morbidity and mortality in humans around the world. This study aimed to provide information on the larvicidal potential of different Citrus species peels against Culex mosquito larvae.Methods: Ethanol extracts of the peels of four Citrus species, such as Citrus sinensis (sweet orange), Citrus reticulata (tangerine), Citrus latifolia (lime), and Citrus paradisi (grape) fruits were tested for larvicidal properties against Culex pipiens at different concentration (3 mg, 5 mg, 7 mg and 8 mg in 100 mL) on 25 larva per concentration. Percentage mortality was recorded for each of the concentrations used. Results: Only Culex latifolia induced the death of all the mosquito larvae (100%) at 5 mg/mL concentration of the extract, meanwhile Culex reticulata resulted in the lowest mortality rate (80%). However, a hundred percent (100%) mortality of the larvae, was observed at 8 mg/mL of all the types of extracts evaluated.Conclusion: The result indicates that the peels of these Citrus species, especially Culex latifolia, hold potential for control of Culex pipiens mosquito larvae.